2019
DOI: 10.3389/fphar.2019.01032
|View full text |Cite
|
Sign up to set email alerts
|

Potential Drug-Drug Interactions in Patients With Urinary Tract Infections: A Contributing Factor in Patient and Medication Safety

Abstract: Introduction: Hospitalized patients with urinary tract infections (UTIs) often present with comorbid illnesses and are subsequently prescribed multiple medications, which increases the likelihood of drug-drug interactions. Therefore, this study aimed to explore the prevalence, levels, risk factors, and clinical relevance of potential drug-drug interactions (pDDIs) in hospitalized patients with UTIs. Secondly, we aimed to develop management guidelines and identify monitoring parameters for the most frequent int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
(68 reference statements)
1
10
2
1
Order By: Relevance
“…Adults aged between 45 and 59 years experienced higher occurrence of potential drug interaction, similarly to previous reports. 30 , 34 , 35 The elderly usually have higher risk of suffering drug interactions, 36 , 37 , 38 but this association was not significant in this study, possibly due to the low number of older participants. We did not observe associations between drug interactions and gender.…”
Section: Discussioncontrasting
confidence: 57%
“…Adults aged between 45 and 59 years experienced higher occurrence of potential drug interaction, similarly to previous reports. 30 , 34 , 35 The elderly usually have higher risk of suffering drug interactions, 36 , 37 , 38 but this association was not significant in this study, possibly due to the low number of older participants. We did not observe associations between drug interactions and gender.…”
Section: Discussioncontrasting
confidence: 57%
“…Potential DDIs (pDDIs) issue has been addressed generally in hospitalized patients [ 8 ] as well as in specific diseases such as liver cirrhosis [ 12 ], hypertension [ 13 ], diabetes mellitus (DM) [ 14 ], bone marrow transplant [ 15 ], cancer [ 16 ], stroke [ 17 ], pneumonia [ 18 ], urinary tract infections [ 19 ], and hepatitis C [ 20 ]. Despite, being one of the most prevalent causes of hospitalization in Pakistan during its emerging season [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the use of these drugs, a large number of other drugs are also prescribed to treat the associated symptoms ijlpr 2022; doi 10.22376/ijpbs/lpr.2022.12.4.P34-40 Pharmacy Practice P-39 and comorbid illnesses. 25 The present study showed that cephalosporins pharmacologic class of antimicrobial drugs were the most-common prescribed antibiotic. This is in agreement with a previous study conducted by other authors 26-28 whereas it is contrary to the result of a study performed by Mohan et al, 29 where amikacin was found to be the most-common prescribed antibiotic in the treatment of UTI.…”
Section: Discussionmentioning
confidence: 67%